THE EFFECT OF TEACHING TECHNIQUES AND INTEREST ON STUDENTS’ ACHIEVEMENT IN READING COMPREHENSION - Busri Busri; Berlin Sibarani; Anni Holila Pulungan (LINGUISTIK TERAPAN, 2018)
The objectives of this study were to find out whether students’ achievement in reading comprehension taught by TELLS technique was significantly higher than PSOT. (2) whether the students’ achievement in reading comprehension with high interest was higher than with low interest, and (3) If there was interaction between teaching techniques and interest on students’ achievement in reading comprehension. This study established the different effect of teaching techniques on students’ interest which was required by the hypothesis and applying experimental research design by using Factorial Design 2x2. Descriptive statistic was used to describe the data such as mean, median, mode, standard deviation, and variance. While inferential statistic used to test the research hypotheses by applying two ways ANOVA with the level of significance 0.05. The results reveals that (1) students’ achievement in reading expository text taught by using TELLS was higer than PSOT technique, with Fob = 17.902 > Ftab = 3.11, (2) students’ achievement in reading expository text on hight interest was higher than that low interest, with Fobs = 38.988 > Ftab = 3.11, (3) there was interaction between teaching technique and interest on students’ achievement in reading comprehension with Fobs = 5.962 > Ftab = 3.11.Keywords:Teaching Techniques, Interest, Reading Comprehension